Desain Dan Realisasi Bandpass Filter 5G Rejection Bandpass Filter Pada Frekuensi 3,7 - 4,2 Ghz - Parlaungan Nasution; Iwan Krisnadi; Agus Sofwan (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2024)
Abstract Fifth Generation, commonly referred to as 5G Technology, is an advanced technology from 4G. 5G technology is considered an effective technology to support the ongoing IoT era and also industry 4.0. The 5G wireless network standard has evolved into the most advanced technology today. Some who have adopted 5G technology include Smart Cities, Internet of Things (IoT). Internet of Things (IoT) and Machine to Machine (M2M) communications on a large scale will utilize the 5G wireless system, so that various requirements will be determined on the network regarding device cost, reliability, energy consumption, latency, and so on. The development of 5G networks is based on New Radio (NR) technology developed by 3GPP as a guide for interfaces to 5G technology. The 5G network system is built quantitatively with the performance parameters determined by ITU-R on 5G technology through IMT-2020. Development of 5G network systems according to future needs and services. The mid-band frequency that will be proposed for the use of the 5G technology frequency is at 3.5 GHz, but this frequency is also used by several satellite communication system operators in Indonesia. Based on the results of the 2019 World Radio Congress, Indonesia received a frequency range of 3500 – 3600 MHz for IMT-Systems (including 5G technology). In fact, based on research conducted by the GSMA, most countries in the Southeast Asian region use the 3400 – 3700 MHz frequency range for the use of satellite communication systems. The trial 5G Frequency Band is n78 (3GPP), namely 3400-3600 MHz, while the current Frequency Band is FSS Ext C-band and C-band, namely 3400-4200 The results of this bandpass filter can pass signals at a frequency of 3.7-4.2 GHz and has a bandwidth of 38 MHz, has a VSWR of 1.28, insertion loss of -3.76 dB and return loss of - 28.293 dB Keywords : 5G, C Band, Bandpass filter